Cotton Stainer, Dysdercus suturellus (Herrich Schaeffer) (Insecta: Hemiptera: Pyrrhocoridae) - Frank W. Mead; Thomas R. Fasulo (EDIS)
Four species of "cotton stainers," also known as "red bugs," are known from Florida. However, the most important of these is the cotton stainer, Dysdercus suturellus (Herrich- Schaeffer). Morrill (1910) stated the cotton stainer was the most destructive cotton pest in Florida. Currently, the cotton stainer is a minor pest of cotton, and then only in the southern part of the state (Sprenkel 2000). This document is EENY-330 (originally published as DPI Entomology Circular 48), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2004. Revised: March 2005.